Proposed Business-To-Business Marketing Strategy For Indibiz Ekspedisi At Pt Telekomunikasi Indonesia - Nadya Amalia (Publikasi Indonesia, 2025)
This study aims to formulate a revised B2B marketing strategy to enhance Indibiz Ekspedisi’s competitiveness and market relevance in Indonesia’s logistics SME segment. A qualitative approach was applied through in-depth interviews with logistics SME decision-makers and internal stakeholders, supported by secondary data. The analysis integrates external perspectives (PESTEL, Porter’s Five Forces, competitor analysis, and consumer analysis) and internal perspectives (STP and 7Ps marketing mix), followed by SWOT and TOWS as the strategic frameworks. This research utilizes the Business Buyer Decision Process framework to examine how each element of the 7Ps affects purchasing decisions among logistics SMEs. The findings reveal key adoption barriers, weak sub-brand visibility, and unclear value communication that hinder market penetration. Based on these insights, the study proposes a refined STP strategy and a restructured 7P marketing mix tailored to the digital logistics context, emphasizing consultative selling, solution bundling, educational promotions, and enhanced onboarding experiences. These integrated strategies aim to bridge strategic gaps and elevate Indibiz Ekspedisi’s positioning in the growing B2B digital logistics ecosystem.